Participation and Local Government - World Bank (Washington, DC, 2012)
Citizen participation in the decisionmaking and development activities of local government can produce more efficient and effective delivery of services by the public sector. In order to foster participation, some responsibility must be devolved from central to local government. However, the assignment of responsibilities to local governments cannot, by itself, ensure participation. Accountable local governments are key actors in any attempt to create an enabling environment for effective participation in public sector activities.